Study of hematological parameters of rats at the action of the immunostimulating drug «Flavovir» (Experimental biology, 2018)
In the conducted research are studied hematologic indicators of blood of rats at effect of “Flavovir” immunoperformance-enhancing drug. It is established that medicine "Flavovir" in a dose of 35 mg/kg at single application causes statistically reliable (Р≤0,001) increase of level of leukocytes, erythrocytes, hemoglobin and hematocrit. Against the background of statistically reliable (Р≤0,001) decrease in level the polymorphonuclear neutrophils, a rise in lymphocytes. Oral introduction of the medicine "Flavovir" stimulates growth of leukocytes 6 days for 60% in a dose of 35 mg/kg, erythrocytes for 33%, hemoglobin to 159,12±0,89g/l, the hematocrit to 52,25±1,76%, lymphocytes on 2,3 times. Level of platelets increases to 838,00±7,56×109/l (Р≤0,001) and increase in percentage of eosinophils for 50% (P≤0,001) compared with control animals. Throughout an experiment change of body weight of rats of rather background values in one of the compared groups was not revealed. Change of water consumption in groups of the animals receiving the studied medicines concerning monitoring was not noted. Comparison of data of measurement of rectal temperature did not reveal reliable differences between experienced and control group of animals. Results of the pilot studies showed that existence of the accruing lymphocytosis can demonstrate activation of a cell-like link of immune system, that is the immunostimulating property of medicine.Key words: immunostimulating drug, «Flavovir», hematological blood counts, rat, experiment.